2013
DOI: 10.1088/1674-1056/22/6/067102
|View full text |Cite
|
Sign up to set email alerts
|

Density-functional theory investigation of electronic structure, elastic properties, optical properties, and lattice dynamics of Ba2ZnWO6

Abstract: The electronic structures, optical dielectric functions, elastic properties, and lattice dynamics of Ba 2 ZnWO 6 have been investigated by using the generalized gradient approximation. The density of states and distributions of charge density show that O and Ba tend toward ionic bond, but O and W or Zn display the covalent bond character. The calculated energy band structure shows that Ba 2 ZnWO 6 is a wide indirect band gap semiconductor. The static value 2.28 of the refractive index is attained. The analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…3). Due to the indirect bandgap nature of this compound, 4–9 the bandgap energy was extrapolated from the intercept of the fitted straight line at F ( R ) = 0 in the F ( hν ) 1/2 versus the energy ( hν ) plot. The bandgap value is found to be 3.74 eV which is slightly smaller than those of some other double perovskites; for example, La 2 MgTiO 6 :Pr 3+ (3.98 eV) 52 and La 2 MgTiO 6 :Er 3+ (4.07 eV).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Due to the indirect bandgap nature of this compound, 4–9 the bandgap energy was extrapolated from the intercept of the fitted straight line at F ( R ) = 0 in the F ( hν ) 1/2 versus the energy ( hν ) plot. The bandgap value is found to be 3.74 eV which is slightly smaller than those of some other double perovskites; for example, La 2 MgTiO 6 :Pr 3+ (3.98 eV) 52 and La 2 MgTiO 6 :Er 3+ (4.07 eV).…”
Section: Resultsmentioning
confidence: 99%
“…3). Due to the indirect bandgap nature of this compound, [4][5][6][7][8][9] the bandgap energy was extrapolated from the intercept of the fitted straight line at F(R) = 0 in the F(hν) 1/2 versus the energy (hν) plot. The bandgap value is found to be…”
Section: Absorption Spectrummentioning
confidence: 99%
See 1 more Smart Citation
“…The Fermi level is set to be zero [39]. As for pristine W 6 O 18 clusters, the O(p) states contribute to the highest valence band and the W(d) states contribute to the bottom of conduction band [14,25,39,40].…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Moreover, it has been reported that the formation of an MPB region in the BNT-BKT-BiCoO 3 system allows further enhancement of the ferroelectric and piezoelectric properties with respect to the BNT-BKT system [10]. On the other hand, BaZn 0.5 W 0.5 O 3 (BZW), which has a cubic perovskite structure with space group of Fm3m [11] is known to be effective for the enhancement of the piezoelectric properties of Pb-based ceramics [12]. However, the effects of BZW addition on the piezoelectric properties of the BNT-BKT system have not been reported to date.…”
Section: Introductionmentioning
confidence: 99%